Lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication and preparation method thereof
By using high-performance borosilicate hollow glass microspheres and specific resin combinations in 5G high-frequency communication materials, combined with hot pressing and forming technology, the balance problem of material mechanics and lightweight needs is solved, and a composite material with low dielectric constant, high mechanical properties and lightweight is achieved, which significantly improves the transmittance of high-frequency signals.
Patent Information
- Application Number
- CN202411693333.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art When developing lightweight high-frequency wave-transmitting composite materials suitable for 5G high-frequency communication, it is difficult to balance the mechanical enhancement effect and lightweight requirements of the material, and there are problems of dielectric constant and thermal viscosity.
By dispersing high-performance borosilicate hollow glass microspheres with solvents and combining liquid polybutadiene, modified polyphenylene ether resin, crosslinking agent and initiator, a resin glue solution with high crosslinking density and network structure was prepared, and the target product was then obtained by hot pressing.
It realizes efficient dispersion of high-performance hollow glass microspheres, reduces the dielectric constant of the composite material, enhances its bending strength and hardness, while maintaining lightweight characteristics, significantly improving the transmittance of high-frequency signals.
Smart Images

Figure CN119526787A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and more specifically, to a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication and a preparation method thereof. Background Art
[0002] With the rapid development of modern satellite radar and 5G communication technology, radars that transmit high-frequency signals have higher and higher requirements for radomes. As an important component of wireless communication equipment, radomes need to have good dielectric properties, high mechanical properties, good molding process performance and low weight to meet the long-distance, high-speed and high-fidelity transmission requirements of high-frequency communication.
[0003] Patent CN116162341A discloses a 5G antenna cover, which uses modified PC resin and modified ASA resin as the matrix, and reduces the dielectric constant of the material while improving the mechanical properties of the material by using basalt fiber, low-dielectric glass fiber and hollow glass microspheres.
[0004] However, although the introduction of hollow glass microspheres can improve the bending strength and hardness of the material while keeping the material lightweight, there are still some limitations, such as the high temperature melting viscosity of the thermoplastic resin matrix, which leads to a limited number of hollow glass microspheres that can be added, and it is difficult to balance the mechanical reinforcement effect and lightweight requirements of the material. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication and a preparation method thereof, which has the advantages of low dielectric constant, high mechanical properties and light weight.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions: a method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, comprising the following steps:
[0007] S1, using a solvent to disperse the hollow glass microspheres, then adding a silane coupling agent solution and stirring at a medium speed, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0008] Continue to use the solvent to dissolve the second resin, and add the first resin, the crosslinking agent and the initiator thereto, and stir at a high speed until the mixture is uniform, to obtain a mixture solution;
[0009] Adding the modified hollow glass microspheres to the mixture solution, stirring at a medium speed until the mixture is uniformly mixed, and ripening to obtain a resin glue solution;
[0010] S2, stacking a plurality of the prepregs, and performing hot pressing and cooling to obtain a target product;
[0011] S3, stacking a plurality of the prepregs in a predetermined order, and forming them by hot pressing, and then cooling them to obtain a target product;
[0012] Among them, the first resin includes at least one of liquid polybutadiene and liquid butadiene-styrene copolymer, the second resin includes at least one of modified polyphenylene ether and modified bismaleimide resin, the hollow glass microspheres are high-performance borosilicate hollow glass microspheres, the cross-linking agent is triallyl isocyanurate, and the initiator is diisopropyl peroxide.
[0013] In one embodiment, the mass fractions of each component in the resin glue are:
[0014] The first resin is 50-100 parts;
[0015] The second resin is 5-50 parts;
[0016] 2.5-25 parts of cross-linking agent;
[0017] Initiator 0.5-5 parts;
[0018] Hollow glass microspheres 50-200 parts.
[0019] In one embodiment, the high-performance borosilicate hollow glass microspheres have a Na content of less than 4.5%, a dielectric loss of less than 0.006, a compressive strength of greater than 4000 psi, a density of 0.2-0.6 g / cm3, a particle size D50 of 15-30 μm, and a particle size D90 of 40-80 μm.
[0020] In one embodiment, the solvent is at least one of butanone and xylene.
[0021] In one embodiment, the basis weight of the glass fiber cloth is 24-105 g / m 2 , the glass fiber cloth is low dielectric glass fiber cloth or alkali-free glass fiber cloth.
[0022] In one embodiment, the silane coupling agent solution is a mixed solution of Y-methacryloxypropyltrimethoxysilane and ethanol.
[0023] In one embodiment, in S1, the speed of the high-speed stirring is 800-2000 rpm, and the speed of the medium-speed stirring is 200-800 rpm.
[0024] In one of the embodiments, in S1, the specific step of aging is: after the mixture solution and the modified hollow glass microspheres are evenly mixed, stirring is continued at a speed of 60-100 rpm for 24 hours.
[0025] In one embodiment, the baking temperature in S2 is 100-200° C., and the baking time is 2-10 min.
[0026] In one embodiment, the hot pressing temperature in S3 is 170-220°C, and the hot pressing pressure ranges from 7-17 kg / cm 2 , hot pressing time is 50-200min.
[0027] A lightweight, high-frequency, wave-transparent composite material suitable for 5G high-frequency communications, prepared by the above-mentioned preparation method.
[0028] The above-mentioned lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication and its preparation method have the following beneficial effects:
[0029] The present invention reduces the viscosity of the resin glue by matching the various components, improves the cross-linking density and network structure of the composite material, and enables high-performance borosilicate hollow glass microspheres to be efficiently dispersed even at high addition amounts. The mass percentage of high-performance borosilicate hollow glass microspheres in the resin solids can exceed 50%, and the volume percentage is as high as 75%.
[0030] A high proportion of hollow glass microsphere filling effectively reduces the dielectric constant of the composite material and enhances the bending strength and hardness of the composite material without affecting its lightweight characteristics. Its dielectric constant at 10GHz is as low as 2.2, while the dielectric loss is reduced to 0.005, thereby significantly improving the transmittance of high-frequency signals and meeting the strict requirements of high-frequency communication antenna covers and related products on material properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION
[0032] The present invention is described in further detail below in conjunction with the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail.
[0033] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0034] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0035] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0036] A method for preparing a lightweight high-frequency wave-transmitting composite material suitable for 5G high-frequency communication, such as Figure 1 As shown, the following steps are included:
[0037] S1, using a solvent to disperse the hollow glass microspheres, then adding a silane coupling agent solution and stirring at a medium speed, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0038] Continue to use the solvent to dissolve the second resin, and add the first resin, the crosslinking agent and the initiator thereto, and stir at a high speed until the mixture is uniform, to obtain a mixture solution;
[0039] Adding the modified hollow glass microspheres to the mixture solution, stirring at a medium speed until the mixture is uniformly mixed, and ripening to obtain a resin glue solution;
[0040] In practical applications, since water has a relatively large polarity and a relatively high boiling point, if it is not removed cleanly during the preparation process, it will easily affect the dielectric properties. Therefore, ethanol is preferably used to prepare the silane coupling agent solution, and the mass ratio of silane coupling agent to ethanol is between 1:1-1:10.
[0041] Furthermore, the mass ratio of the solvent used to pre-disperse the hollow glass microspheres to the hollow glass microspheres is in the range of 1:1 to 5:1, and the preferred mass ratio is in the range of 1.5:1 to 2.5:1, which is used to ensure the dispersion of the hollow glass microspheres. In addition, the silane coupling agent can dissociate an appropriate amount of Si-OH in water and ethanol, commonly known as hydrolysis, which can react with the Si-OH on the surface of the hollow glass microspheres to generate -SiOSi- and water, so that the silane coupling agent has a higher reactivity, so as to enhance the chemical bonding between the hollow glass microspheres and the resin, effectively avoid the floating and stratification of the hollow glass microspheres and improve the interface bonding.
[0042] Furthermore, the mass ratio of the solvent used to dissolve the second resin to the second resin is greater than 1:1 to ensure complete dissolution of the second resin. Finally, the modified hollow glass microspheres are added to the mixture solution, stirred at a medium speed until the mixture is uniformly mixed, and then stirred and matured at a low speed to allow the -C=C- on the silane coupling agent grafted on the surface of the hollow glass microspheres to undergo a moderate grafting reaction with the hydrocarbon resin, the polyphenylene ether resin, and the crosslinking aid to avoid floating and stratification of the hollow glass microspheres.
[0043] S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg;
[0044] The process parameters of gluing are determined by the gelation time of the resin glue, the physical properties of the semi-cured sheet to be prepared, the gluing equipment used, etc. The main physical properties of the semi-cured sheet include resin content and resin fluidity. Specifically, during the impregnation process, since the density of the hollow glass microspheres is lower than the density of the resin, the hollow glass microspheres are easy to float and cause stratification during the impregnation process, which in turn affects the uniformity and stability of the prepared semi-cured sheet. In order to avoid this problem, a stirring step can be introduced during the impregnation process to ensure the uniform distribution of the hollow glass microspheres in the resin.
[0045] S3, stacking a plurality of prepregs, forming them by hot pressing, and then cooling them to obtain a target product;
[0046] In actual production, the laminated structure of the prepregs can be prepregs of the same specifications stacked together and hot pressed, or prepregs of different specifications can be stacked together and hot pressed as needed to achieve structural optimization. Specifically, prepregs with a slightly lower microsphere content can be placed on the upper and lower surface layers to obtain a relatively smoother appearance, and prepregs with a higher microsphere content can be placed on the inner layer to enhance the strength and rigidity of the overall structure. In addition, the lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication prepared by the present invention can not only be used alone, but can also be used as a core material together with other materials to prepare a sandwich structure or a sandwich structure for use to meet different application requirements and performance requirements.
[0047] Specifically, the first resin includes at least one of liquid polybutadiene and liquid butadiene-styrene copolymer, the second resin includes at least one of modified polyphenylene ether and modified bismaleimide resin, and the hollow glass microspheres are high-performance borosilicate hollow glass microspheres.
[0048] The first resin is a low-polar hydrocarbon resin, and its molecular chain contains unsaturated double bonds, so that it can be converted into a thermosetting system through a cross-linking curing reaction, and the curing process must be controllable to meet the preparation process of the semi-cured sheet. In addition, the molecular chain also contains C-H bonds with very low polarity, so the first resin has excellent dielectric properties, a dielectric constant of 2.4-2.8 at 1MHz, a dielectric loss of 0.0002-0.0006, and good fluidity at room temperature, which helps to achieve full impregnation of glass fiber cloth and ensure good bonding between the resin and the reinforcing material in the composite material, but it also easily causes the prepared semi-cured sheet to become sticky. Therefore, it is necessary to further add the second resin and a large amount of high-performance borosilicate hollow glass microspheres to improve the stickiness of the semi-cured sheet.
[0049] The second resin is an engineering plastic with excellent performance. Its structure is an aromatic ring high-rigidity skeleton chain, and it has no hydrolyzable groups and polar groups. This structure enables it to have excellent heat resistance, hydrolysis stability, low moisture absorption, good dimensional stability, flame retardancy and excellent adhesion, especially excellent and stable dielectric properties in a wide temperature range. The second resin and the first resin are used in combination to solve the problems of weak interlayer bonding, low bending strength and surface stickiness of the first resin after curing, which helps to keep the antenna cover lightweight while enhancing its mechanical properties, weather resistance and chemical resistance, ensuring the long-term stable operation of the antenna cover under various climatic conditions.
[0050] Hollow glass microspheres are high-performance borosilicate hollow glass microspheres. Their high-strength sphere walls and hollow structures can give them the characteristics of high strength, low dielectric constant and low density. Moreover, through the application of wet process, a higher addition ratio can be achieved in the composite material, which can significantly reduce the density of the composite material and help reduce the weight of the radome while maintaining the low dielectric loss and strength of the material. In addition, hollow glass microspheres also help improve the thermal insulation performance of the composite material, which is beneficial for maintaining the performance of the radome in high temperature environments.
[0051] Specifically, the crosslinking agent is triallyl isocyanurate (TAIC), which reacts with polymer chains to form a crosslinked network, further increasing the crosslinking density of the polymer, thereby enhancing the heat resistance, mechanical strength and dimensional stability of the material.
[0052] Specifically, the initiator is dicumyl peroxide (DCP), which decomposes during heating to produce free radicals, initiating polymerization reactions in the resin and ensuring that the material can be cured at a specific temperature.
[0053] Specifically, the silane coupling agent is Y-methacryloxypropyl trimethoxysilane, and this silane coupling agent containing -C=C- has a lower polarity than silane coupling agents containing other functional groups, such as amino groups, and therefore does not increase the dielectric loss of the composite material. In addition, the -C=C- double bond in the silane coupling agent is more likely to form a cross-linked network with hydrocarbon resin. At the same time, due to the high addition ratio of hollow glass microspheres, the resin layer covering the outer surface of the hollow glass microspheres is relatively thin, and the hollow glass microspheres are relatively easier to be penetrated by water vapor. The use of silane coupling agents to modify hollow glass microspheres can solve the problem of high dielectric loss caused by the silicon hydroxyl groups on the surface of hollow glass microspheres absorbing highly polar water.
[0054] The present invention reduces the viscosity of the resin glue by matching the various components, improves the cross-linking density and network structure of the composite material, and enables high-performance borosilicate hollow glass microspheres to be efficiently dispersed even at high addition amounts. The mass percentage of high-performance borosilicate hollow glass microspheres in the resin solids can exceed 50%, and the volume percentage is as high as 75%.
[0055] A high proportion of hollow glass microsphere filling effectively reduces the dielectric constant of the composite material and enhances the bending strength and hardness of the composite material without affecting its lightweight characteristics. Its dielectric constant at 10GHz is as low as 2.2, while the dielectric loss is reduced to 0.005, thereby significantly improving the transmittance of high-frequency signals and meeting the strict requirements of high-frequency communication antenna covers and related products on material properties.
[0056] Specifically, the mass fractions of the components in the resin glue are: 50-100 parts of the first resin; 5-50 parts of the second resin; 2.5-25 parts of the crosslinking agent; 0.5-5 parts of the initiator; 50-200 parts of the hollow glass microspheres. The mass fraction of the hollow glass microspheres in the resin glue is preferably 80-160 parts.
[0057] In production practice, each component of the resin glue (except the solvent) is calculated by weight of the non-volatile matter. When preparing the resin glue, the solid content in the glue can be adjusted by adding an appropriate amount of solvent to make the solid content reach a range of 50% to 75%, preferably 65%. Such a solid content level can balance the viscosity and fluidity of the resin glue, ensuring that it can fully impregnate the glass fiber cloth without being too viscous to cause processing difficulties.
[0058] Specifically, the high-performance borosilicate hollow glass microspheres have a Na content of less than 4.5%, a dielectric loss of less than 0.006, a compressive strength of more than 4000psi, and a density of 0.2-0.6g / cm 3 , particle size D50 is 15-30μm, and particle size D90 is 40-80μm.
[0059] In practical applications, since small-particle-size, low-Na-content high-performance borosilicate hollow glass microspheres have better compressive strength and lower dielectric loss coefficient, the Na content of high-performance borosilicate hollow glass microspheres is preferably less than 4.0%, the dielectric loss is preferably less than 0.005, the compressive strength is preferably greater than 6000psi, and the density is preferably 0.3-0.5g / cm 3 , particle size D50 is 20-30μm, and particle size D90 is 40-60μm.
[0060] Specifically, the solvent is at least one of butanone and xylene, which is used to dissolve and disperse other components and adjust the viscosity to a suitable range to facilitate gluing.
[0061] Specifically, the basis weight of the glass fiber cloth is 24-105g / m 2 The glass fiber cloth is low dielectric glass fiber cloth (D-gl ass) or alkali-free glass fiber cloth (E-gl ass), preferably low dielectric glass fiber cloth, to further reduce the dielectric constant of the composite material. In actual production, glass fiber cloths with different basis weights can be selected as needed, such as a basis weight of 24g / m 2 106 glass fiber cloth, basis weight is 48g / m 2 1080 glass fiber cloth, basis weight is 78g / m 2 2113 glass fiber cloth, basis weight is 105g / m 2 2116 fiberglass cloth, etc.
[0062] Specifically, the silane coupling agent solution is a mixed solution of Y-methacryloxypropyltrimethoxysilane and ethanol, and the preparation steps are: first, the silane coupling agent is added to the ethanol solution, and after stirring evenly, the silane coupling agent solution is obtained. Among them, the amount of the silane coupling agent Y-methacryloxypropyltrimethoxysilane added in S1 is between 0.5% and 1.5% of the amount of the hollow glass microspheres added.
[0063] Specifically, the high-speed stirring speed in S1 is 800-2000 rpm, preferably 1200-1500 rpm, and the stirring time at room temperature is at least 1 hour; the medium-speed stirring speed is 200-800 rpm, preferably 400-600 rpm, and the stirring time is 0.5-5 hours, preferably 1-3 hours.
[0064] Specifically, in S1, the specific steps of aging are as follows: after the mixture solution and the modified hollow glass microspheres are evenly mixed, stirring is continued at a speed of 60-100 rpm for 24 hours, so that the silanol group in the Y-methacryloxypropyltrimethoxysilane forms a stable silicon-oxygen bond with the surface of the hollow glass microspheres, and at the same time promotes the copolymerization reaction of the methacryloxy group with the resin, as well as the curing reaction of the liquid polybutadiene and modified polyphenylene ether resin in the resin with the crosslinking agent and initiator to form a crosslinking network, thereby completing the aging process, ensuring the high dispersion of the hollow glass microspheres in the resin glue and the strengthening of the interface bonding, and improving the overall performance of the composite material.
[0065] Specifically, the baking temperature in S2 is 100-200°C, and the baking time is 2-10 minutes; preferably, the baking temperature is 130-160°C, and the baking time is 3-6 minutes. The resin fluidity of the semi-cured sheet is adjusted by controlling the baking time to facilitate the subsequent hot pressing molding process.
[0066] Specifically, the hot pressing temperature in S3 is 170-220°C, preferably 185-205°C; the hot pressing pressure range is 7-17 kg / cm 2 , preferably 10-15kg / cm 2 The pressure can be applied in stages; the hot pressing time is 50-200 min, preferably 90-150 min.
[0067] Hot pressing molding requires maintaining a certain time at high temperature and a certain pressure to further solidify the resin, so choosing the appropriate hot pressing temperature, pressure and time can ensure that the resin flows fully and fills all spaces while avoiding over-curing or damaging the hollow glass microspheres.
[0068] A lightweight, high-frequency, wave-transparent composite material suitable for 5G high-frequency communications, prepared by the above-mentioned preparation method.
[0069] Example 1
[0070] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0071] S1, first add 2.5 parts of Y-methacryloxypropyltrimethoxysilane to 15 parts of ethanol solution to obtain a silane coupling agent solution;
[0072] Use 180 parts of butanone solvent to disperse 105 parts of a density of 0.46 g / cm 3 High-performance borosilicate hollow glass microspheres, and then adding silane coupling agent solution, stirring at a speed of 400 rpm for 1 hour, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0073] 25 parts of modified polyphenylene ether resin were dissolved in 160 parts of butanone solvent, and 90 parts of liquid polybutadiene resin, 10 parts of liquid butadiene-styrene copolymer, 10 parts of triallyl isocyanurate and 2 parts of dicumyl peroxide were added thereto, and stirred at a high speed of 1500 rpm for 1 hour until the mixture was uniformly mixed to obtain a mixture solution;
[0074] Add the modified hollow glass microspheres to the mixture solution, stir at a medium speed of 400 rpm for 3 hours until the mixture is uniformly mixed, and then continue stirring at a speed of 80 rpm for 24 hours to complete the aging process to obtain a resin glue solution;
[0075] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue solution until it was completely soaked, then taken out and baked in a 150°C oven for 4 minutes to obtain a semi-cured sheet with a resin content RC value of 42% and a resin fluidity RF of 1.5%.
[0076] S3, stack 20 prepregs of the same specifications cut at zero degree in a predetermined order and form them by hot pressing at a temperature of 190°C and a pressure of 7kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After hot pressing for 160 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0077] Example 2
[0078] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0079] S1, first add 2.0 parts of Y-methacryloxypropyltrimethoxysilane to 12 parts of ethanol solution to obtain a silane coupling agent solution;
[0080] Use 260 parts of butanone solvent to disperse 105 parts of a density of 0.32 g / cm 3 High-performance borosilicate hollow glass microspheres, and then adding silane coupling agent solution, stirring at a speed of 300 rpm for 1 hour, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0081] 160 parts of butanone solvent was used to dissolve 20 parts of modified polyphenylene ether resin, and 80 parts of liquid polybutadiene resin, 20 parts of liquid butadiene-styrene copolymer, 15 parts of triallyl isocyanurate and 2.3 parts of dicumyl peroxide were added thereto, and stirred at a high speed of 1500 rpm for 1 hour until the mixture was uniformly mixed to obtain a mixture solution;
[0082] Add the modified hollow glass microspheres to the mixture solution, stir at a medium speed of 300 rpm for 3 hours until the mixture is uniformly mixed, and then continue stirring at a speed of 80 rpm for 24 hours to complete the aging process to obtain a resin glue solution;
[0083] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue solution until it was completely soaked, then taken out and baked in a 150°C oven for 4.5 minutes to obtain a semi-cured sheet with a resin content RC value of 45% and a resin fluidity RF of 0.5%.
[0084] S3, 15 zero-degree cut semi-cured sheets of the same specifications are stacked in a predetermined order and formed by hot pressing at a temperature of 190°C and a pressure of 7kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 130 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0085] Example 3
[0086] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0087] S1, first add 0.7 parts of Y-methacryloxypropyltrimethoxysilane to 6 parts of ethanol solution to obtain a silane coupling agent solution;
[0088] Use 95 parts of butanone solvent to disperse 55 parts of a density of 0.46 g / cm 3 High-performance borosilicate hollow glass microspheres, and then adding silane coupling agent solution, stirring at a speed of 500 rpm for 1 hour, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0089] 120 parts of butanone solvent were used to dissolve 45 parts of modified polyphenylene ether resin and 5 parts of modified bismaleimide resin, and 75 parts of liquid polybutadiene resin, 10 parts of triallyl isocyanurate and 1.2 parts of dicumyl peroxide were added thereto, and stirred at a high speed of 1300 rpm for 1 hour until the mixture was uniformly mixed to obtain a mixture solution;
[0090] Add the modified hollow glass microspheres to the mixture solution, stir at a medium speed of 500 rpm for 2 hours until the mixture is evenly mixed, and then continue stirring at a speed of 80 rpm for 24 hours to complete the aging process to obtain a resin glue solution;
[0091] S2, the basis weight is 105g / m 2The 2116 glass fiber cloth was immersed in the resin glue solution until it was completely soaked, then taken out and baked in a 150°C oven for 5 minutes to obtain a semi-cured sheet with a resin content RC value of 45% and a resin fluidity RF of 2.5%.
[0092] S3, stack 20 prepregs of the same specifications cut at zero degree in a predetermined order and form them by hot pressing at a temperature of 190°C and a pressure of 7kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After hot pressing for 160 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0093] Example 4
[0094] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0095] S1, first add 3 parts of Y-methacryloxypropyltrimethoxysilane to 15 parts of ethanol solution to obtain a silane coupling agent solution;
[0096] Use 260 parts of butanone solvent to disperse 105 parts of a density of 0.32 g / cm 3 High-performance borosilicate hollow glass microspheres, and then adding silane coupling agent solution, stirring at a speed of 300 rpm for 1 hour, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres;
[0097] 15 parts of modified polyphenylene ether resin were dissolved in 160 parts of butanone solvent, and 65 parts of liquid polybutadiene resin, 35 parts of liquid butadiene-styrene copolymer, 20 parts of triallyl isocyanurate and 3.3 parts of dicumyl peroxide were added thereto, and stirred at a high speed of 1300 rpm for 1 hour until the mixture was uniformly mixed to obtain a mixture solution;
[0098] Add the modified hollow glass microspheres to the mixture solution, stir at a medium speed of 300 rpm for 3 hours until the mixture is uniformly mixed, and then continue stirring at a speed of 80 rpm for 24 hours to complete the aging process to obtain a resin glue solution;
[0099] S2, the basis weight is 48g / m 2 The 1080 glass fiber cloth was immersed in the resin glue solution until it was completely soaked, then taken out and baked in a 150°C oven for 3.5 minutes to obtain a semi-cured sheet with a resin content RC value of 67% and a resin fluidity RF of 0.3%.
[0100] S3, 15 zero-degree cut semi-cured sheets of the same specifications are stacked in a predetermined order and formed by hot pressing at a temperature of 190°C and a pressure of 7kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 170 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0101] Example 5
[0102] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0103] The prepregs were stacked in the following order: one 2116RC45 prepreg prepared in Example 3 was used for each of the upper and lower layers, and 13 1080RC67 prepregs prepared in Example 4 were used for the middle surface layer; and then hot pressing was performed at a temperature of 190°C and a pressure of 7 kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 170 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0104] Comparative Example 1
[0105] This comparative example provides a composite material, and the specific preparation steps are as follows:
[0106] S1, adding 65 parts of bisphenol A epoxy resin with an epoxy equivalent of 450 g / eq and 35 parts of bisphenol A epoxy resin with an epoxy equivalent of 185 g / eq to 37 parts of acetone, stirring and dispersing them uniformly to obtain a first solution;
[0107] 3.4 parts of dicyandiamide and 0.06 parts of 2-methylimidazole were added to 66 parts of ethylene glycol monomethyl ether, and dissolved and dispersed uniformly to obtain a second solution;
[0108] The second solution was added to the first solution and stirred evenly. Then 78.5 parts of a density of 0.38 g / cm 3 Add conventional borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0109] S2, immerse the 1080 glass fiber cloth into the resin glue solution, take it out after it is completely soaked, and bake it in a 150°C oven for 3.5 minutes to obtain a semi-cured sheet, whose resin content RC value is 67% and resin fluidity RF is 0.3%;
[0110] S3, stack 18 prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press the temperature from 120°C to 160°C in stages, and heat press pressure from 7kg / cm2 Stepwise pressurization up to 10kg / cm 2 , and then heat-pressed at 160°C for 150 min, cooled to room temperature, and disassembled to obtain the target product.
[0111] Comparative Example 2
[0112] This embodiment provides a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, and the specific preparation steps are as follows:
[0113] 15 parts of modified polyphenylene ether resin were dissolved in 160 parts of butanone solvent, and 65 parts of liquid polybutadiene resin, 35 parts of liquid butadiene-styrene copolymer, 22 parts of triallyl isocyanurate and 3.3 parts of dicumyl peroxide were added thereto, and stirred at a high speed of 1300 rpm for 1 hour until the mixture was uniformly mixed to obtain a mixture solution;
[0114] Add 105 parts of a 0.32 g / cm 3 High-performance borosilicate hollow glass microspheres were stirred at a medium speed of 300 rpm for 3 hours until they were evenly mixed, and then stirred at a speed of 80 rpm for 24 hours to complete the aging process and obtain a resin glue solution;
[0115] S2, the basis weight is 48g / m 2 The 1080 glass fiber cloth was immersed in the resin glue solution until it was completely soaked, then taken out and baked in a 150°C oven for 3.5 minutes to obtain a semi-cured sheet with a resin content RC value of 67% and a resin fluidity RF of 0.3%.
[0116] S3, 15 zero-degree cut semi-cured sheets of the same specifications are stacked in a predetermined order and formed by hot pressing at a temperature of 190°C and a pressure of 7kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 170 min, the mixture was taken out and transferred to a cold press to be cooled to 25°C to obtain the target product.
[0117] In the first resin, the liquid polybutadiene is Ricon 154 produced by Cray Valley (Guangzhou) Chemical Co., Ltd., B-3000 produced by Nippon Soda, or YH LBR 1504 produced by Shandong Yuhuang Chemical Co., Ltd., and the liquid butadiene-styrene copolymer is Ricon 181 produced by Cray Valley (Guangzhou) Chemical Co., Ltd.
[0118] In the second resin, the modified polyphenylene ether used is SA-9000 produced by Sabic or SQP1201 produced by Shandong Shengquan New Materials Co., Ltd. The modified bismaleimide resin used is TBM7200 produced by Tongyu New Materials (Guangdong) Co., Ltd.
[0119] Among the above hollow glass microspheres, the high-performance borosilicate hollow glass microspheres are H32HS or H46HS produced by Zhongke Yali Technology Co., Ltd., or S3240 or S4630 produced by 3M Company. The density is 0.38g / cm 3 The common borosilicate hollow glass microspheres used are the H38 model produced by Zhongke Yali Technology Co., Ltd. or the VS5500 model produced by 3M.
[0120] The relevant performance tests were carried out on each embodiment and comparative example, and the results are as follows:
[0121]
[0122] Table 1
[0123] Table 1 records the density, bending strength, dielectric constant at 10 GHz, and dielectric loss of each embodiment and comparative example. In each embodiment using the combination of the first resin, the second resin, and the high-performance borosilicate hollow glass microspheres, the dielectric loss at 10 GHz is less than 0.005, which not only maintains the characteristics of lightweight, but also shows excellent bending strength; the present invention increases the addition amount of high-performance borosilicate hollow glass microspheres, so that the prepared composite material has excellent low dielectric constant, high mechanical properties and lightweight characteristics, significantly improves the transmittance of high-frequency signals, and meets the strict requirements of high-frequency communication antenna covers and related products on material properties.
[0124] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication, characterized in that: The following steps are involved: S1, using a solvent to disperse the hollow glass microspheres, then adding a silane coupling agent solution and stirring at a medium speed, and filtering out the solvent after mixing evenly to obtain modified hollow glass microspheres; Continue to use the solvent to dissolve the second resin, and add the first resin, the crosslinking agent and the initiator thereto, and stir at a high speed until the mixture is uniform, to obtain a mixture solution; Adding the modified hollow glass microspheres to the mixture solution, stirring at a medium speed until the mixture is uniformly mixed, and ripening to obtain a resin glue solution; S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg; S3, stacking a plurality of the prepregs, and performing hot pressing and cooling to obtain a target product; Among them, the first resin includes at least one of liquid polybutadiene and liquid butadiene-styrene copolymer, the second resin includes at least one of modified polyphenylene ether and modified bismaleimide resin, the hollow glass microspheres are high-performance borosilicate hollow glass microspheres, the cross-linking agent is triallyl isocyanurate, and the initiator is diisopropyl peroxide.
2. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The mass fractions of each component in the resin glue are: The first resin is 50-100 parts; The second resin is 5-50 parts; 2.5-25 parts of cross-linking agent; Initiator 0.5-5 parts; Hollow glass microspheres 50-200 parts.
3. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The high-performance borosilicate hollow glass microspheres have a Na content of less than 4.5%, a dielectric loss of less than 0.006, a compressive strength of more than 4000 psi, and a density of 0.2-0.6 g / cm 3 , particle size D50 is 15-30μm, and particle size D90 is 40-80μm.
4. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The solvent is at least one of butanone and xylene.
5. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The basis weight of the glass fiber cloth is 24-105g / m 2 , the glass fiber cloth is low dielectric glass fiber cloth or alkali-free glass fiber cloth.
6. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The silane coupling agent solution is a mixed solution of Y-methacryloxypropyltrimethoxysilane and ethanol.
7. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: In S1, the speed of the high-speed stirring is 800-2000 rpm, and the speed of the medium-speed stirring is 200-800 rpm.
8. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: In S1, the specific step of aging is: after the mixture solution and the modified hollow glass microspheres are evenly mixed, stirring is continued at a speed of 60-100 rpm for 24 hours.
9. The method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to claim 1, characterized in that: The baking temperature in S2 is 100-200°C, and the baking time is 2-10 minutes; the hot pressing temperature in S3 is 170-220°C, and the hot pressing pressure range is 7-17 kg / cm 2 , hot pressing time is 50-200min.
10. A lightweight high-frequency wave-transmitting composite material suitable for 5G high-frequency communication, characterized in that: The composite material is prepared according to the method for preparing a lightweight high-frequency wave-transparent composite material suitable for 5G high-frequency communication according to any one of claims 1-9.
Citation Information
Patent Citations
5G antenna housing
CN116162341A
Lightweight high-strength composite material and preparation method thereof
CN102276960A
Laminated material and preparation method and hollow glass microsphere application thereof
CN103287032A
Preparation method of novel ABS (Acrylonitrile Butadiene Styrene) resin-based material
CN109401180A
Hydrocarbon resin composition as well as preparation method and application thereof
CN111154197A